. Pengaruh Ekaristi terhadap Kehidupan Sosial Anggota Komunitas Tritunggal Mahakudus, Yogyakarta - Cornelius Satrio Tonapa; Yohanes Subali; Adris Musu Sili (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2026)
The Eucharist for the Church is seen as the culmination of the whole life of faith. The Eucharist influences the faithful who participate in it in the form of spiritual and social values. This study aims to examine the relationship between participation in the Eucharist and the implementation of social values in members of the Holy Trinity Community (KTM). Quantitative method was applied with data collection technique through questionnaires to 50 members of KTM. The results of the analysis show that the intensity of participation in the Eucharist is directly proportional to the level of appreciation of social values. Those participating in the Eucharist are also active in social activities. The research findings prove that there is a connection between spiritual life and social practices in religious communities. Where, participation in the Eucharist encourages greater involvement in social life.